Determination of Phylogenetic and Molecular Characteristics of Three Malaysian Ginger Cultivars (Zingiber officinale Roscoe) Using Microsatellite DNA - Harith Jameel Mahdi; Retno Andayani; Ishak Aziz (Tropical Life Sciences Research, 2013)
Three Malaysian ginger cultivars (Bukit Tinggi, Tanjung Sepat and Sabah) were collected and examined for genetic polymorphisms using microsatellite DNA primers. The single microsatellite oligonucleotide primers (CATA)5, (GATA)5 and (GAC)6 were used in polymerase chain reactions (PCRs). These PCR reactions produced 7 polymorphic bands with an average of 2.334 polymorphic bands per primer, leading to an average polymorphism rate of 17.9%. Cluster analysis revealed 87.50% similarity between Bukit Tinggi and Tanjung Sepat, 64.27% similarity between Bukit Tinggi and Sabah and 56.25% similarity between Tanjung Sepat and Sabah. DNA sequencing of the polymorphic PCR products of Tanjung Sepat ginger revealed the characteristic features of a putative new gene: a core promoter sequence, an enhancer and a transcription start site. Cluster analysis using the unweighted pair group method with arithmetic average (UPGMA) was used to construct a phylogenetic tree, which indicated that Bukit Tinggi ginger is genetically more closely related to Tanjung Sepat ginger than to Sabah ginger. Based on the results of this study, we concluded that there is genotypic variation among ginger cultivars, and the microsatellite DNA primers described here are useful for detecting polymorphic DNA in Malaysian ginger cultivars. Additionally, these microsatellite DNA primers may be used as molecular markers for discriminating among select Malaysian ginger cultivars. Tiga kultivar halia Malaysia (Bukit Tinggi, Tanjung Sepat dan Sabah) telah dikumpul dan diperiksa untuk polimorfisme genetik menggunakan primer DNA mikrosatelit. Primer oligonukleotida mikrosatelit tunggal (CATA)5, (GATA)5 dan (GAC)6 telah digunakan dalam reaksi rantai polimerase (PCR). Reaksi PCR ini telah menghasilkan 7 jalur polimorfik dengan purata 2.334 jalur per primer, dengan kadar purata polimorfisme 17.9%. Analisis kluster telah menunjukkan bahawa terdapat 87.50% persamaan antara Bukit Tinggi dan Tanjung Sepat, 64.27% persamaan antara Bukit Tinggi dan Sabah dan 56.25% persamaan antara Tanjung Sepat dan Sabah. Jujukan DNA produk polimorfik PCR menunjukkan ciri-ciri gen baru: satu jujukan promoter teras, satu penggalak dan satu lokasi mula transkripsi. Analisis kluster menggunakan unweighted pair group method with arithmetic average (UPGMA) telah digunakan untuk membina pokok filogenetik, yang telah menunjukkan bahawa halia Bukit Tinggi lebih mempunyai hubungan dengan halia Tanjung Sepat berbanding halia Sabah. Berdasarkan dapatan kajian ini, kami telah membuat kesimpulan bahawa terdapat variasi genotipik antara kultivar halia, dan primer mikrosatelit DNA yang telah dihuraikan disini berguna untuk mengesan DNA polimorfik kultivar halia Malaysia. Selain itu, primer mikrosatelit DNA ini boleh digunakan sebagai penanda molekul untuk membezakan kultivar terpilih halia Malaysia.